2001
DOI: 10.1021/ja011021b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Containing Functional Groups on Single-Wall Carbon Nanotubes:  NEXAFS and Vibrational Spectroscopic Studies

Abstract: Single-walled nanotubes (SWNTs) produced by plasma laser vaporization (PLV) and containing oxidized surface functional groups have been studied for the first time with NEXAFS. Comparisons are made to SWNTs made by catalytic synthesis over Fe particles in high-pressure CO, called HiPco material. The results indicate that the acid purification and cutting of single-walled nanotubes with either HNO3/H2SO4 or H2O2/H2SO4 mixtures produces the oxidized groups (O/C = 5.5-6.7%), which exhibit both pi*(CO) and sigma*(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
395
2
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(433 citation statements)
references
References 30 publications
31
395
2
5
Order By: Relevance
“…6 The aromatic ring system of the SWNTs can be disrupted by the application of extremely aggressive reagents. When sonicated 51 in the presence of strong oxidizing agents such as HNO 3 or H 2 SO 4 or a mixture of the two, 52 the nanotubes can be functionalized as carboxylic acids or quinones, [53][54][55][56] whereas sonication in organic solvents produces dangling bonds in the SWNTs that undergo further chemical reactions. 57 As expected from the foregoing discussion, the oxidative power necessary to incorporate acidic sites into carbon nanotubes varies with the tube diameter.…”
Section: Electronic Structure and Chemical Reactivitymentioning
confidence: 99%
“…6 The aromatic ring system of the SWNTs can be disrupted by the application of extremely aggressive reagents. When sonicated 51 in the presence of strong oxidizing agents such as HNO 3 or H 2 SO 4 or a mixture of the two, 52 the nanotubes can be functionalized as carboxylic acids or quinones, [53][54][55][56] whereas sonication in organic solvents produces dangling bonds in the SWNTs that undergo further chemical reactions. 57 As expected from the foregoing discussion, the oxidative power necessary to incorporate acidic sites into carbon nanotubes varies with the tube diameter.…”
Section: Electronic Structure and Chemical Reactivitymentioning
confidence: 99%
“…28,29 The purification of carbon nanotubes is mainly done to remove any metal catalyst and amorphous carbon, although this yields small amounts of oxygen-containing functional groups, such as carboxylic groups. 30 However, these groups mainly are located at the open ends of the CNTs, so the hydrophobic surface of CNTs still remaining and will not affect the interaction of TBO and MWNTs. Figure 1 displays the typical morphology of the MWNTs (A) and TBO-MWNTs (B) characterized by scanning electron microscopy (SEM).…”
Section: Tbo Assembled Onto the Surface Of Mwnts And The Characterizamentioning
confidence: 99%
“…The results indicate that KMnO 4 creates an oxidized tube that is free from amorphous carbon; however, additional steps are needed to remove the MnO 2 that is generated during the oxidation process. Kuznetsova et al [32] have demonstrated that both carbonyl and ether groups are produced when SWNTs are purified using H 2 SO 4 /HNO 3 and H 2 SO 4 /H 2 O 2 mixtures. The effect of partial chemical oxidation of SWNTs using various oxidizing agents has also been reported by Yang and co-workers [19].…”
Section: Introductionmentioning
confidence: 99%